(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper analyzes the evolution of the various measures with which, since the end of the last century, the irregular aliens has been deprived of their liberty: first with deprivation of liberty in criminal cases, then with administrative detention in Detention Centers for Repatriation and Hotspots. The text reconstructs the complex events that accompanied the development of this discipline on personal liberty for irregular aliens, seeking to highlight the reasons behind this development and its critical issues.